EVALUATING A PROBLEM-BASED LEARNING PHYSICS E-MODULE FOR STATIC ELECTRICITY - Dwi Novia Rosna (Physics and Science Education Journal (PSEJ), 2025)
This study aimed to examine the effectiveness of a Problem-Based Learning (PBL) based physics e-module on the topic of static electricity. The study employed a Research and Development (R&D) method using the 4-D development model, which consists of the define, design, develop, and disseminate stages. The research subjects were students of class XII MIPA 2 and XII MIPA 3, selected randomly, and involved a small-group trial conducted during the development stage and a limited field trial conducted during the dissemination stage. The data were quantitative and obtained from learning outcome tests in the form of pre-test and post-test scores, which were analyzed using N-Gain analysis. The results showed that the small-group trial produced an N-Gain score of 0.76, categorized as moderate, with an effectiveness percentage of 76% (effective). Meanwhile, the limited field trial yielded an N-Gain score of 0.55, categorized as moderate, with an effectiveness percentage of 55% (moderately effective). These findings indicate that the PBL-based physics e-module is effective in improving students’ learning outcomes on static electricity. The implications of this study suggest that PBL-based e-modules can serve as an alternative digital learning medium to support more active, contextual, and problem-oriented physics learning.